2022
DOI: 10.1093/plcell/koac317
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber STACHYOSE SYNTHASE is regulated by its cis-antisense RNA asCsSTS to balance source–sink carbon partitioning

Abstract: Photosynthate partitioning between source and sink is a key determinant of crop yield. In contrast to sucrose-transporting plants, cucumber (Cucumis sativus) plants mainly transport stachyose and stachyose synthase (CsSTS) synthesizes stachyose in the vasculature for loading. Therefore, CsSTS is considered a key regulator of carbon partitioning. We found that CsSTS expression and CsSTS enzyme activity were upregulated in the vasculature and downregulated in mesophyll tissues at fruiting. In situ hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…As previously demonstrated, larger starch granules promote the destruction of thylakoid lamellae and then a secondary reduction in the photosynthetic rate [79]. Furthermore, favourable conditions must be present for phloem loading, which appear to be regulated by genes of the type CsSTS (Cucumis sativus stachyose synthase) [80], StSUT2 (Spondias tuberosa sucrose transporter 2) [81], and SWEET4 superfamily of genes [82]. However, when the metabolism is reduced, the expression of genes involved in phloem loading may also be compromised, and as a consequence, more starch granules are formed into the chloroplast [83][84][85].…”
Section: Discussionmentioning
confidence: 91%
“…As previously demonstrated, larger starch granules promote the destruction of thylakoid lamellae and then a secondary reduction in the photosynthetic rate [79]. Furthermore, favourable conditions must be present for phloem loading, which appear to be regulated by genes of the type CsSTS (Cucumis sativus stachyose synthase) [80], StSUT2 (Spondias tuberosa sucrose transporter 2) [81], and SWEET4 superfamily of genes [82]. However, when the metabolism is reduced, the expression of genes involved in phloem loading may also be compromised, and as a consequence, more starch granules are formed into the chloroplast [83][84][85].…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that in the sucrose metabolism pathway, gene expression and enzyme activity associated with sucrose catabolism (SUS, invertase, etc.) decrease under low source-sink ratio conditions [ 16 ]. In our work, two SUS genes ( CsaV3_4G000970 and CsaV3_5G020420 ) were downregulated in FNLs, suggesting that a feedback regulatory mechanism in the sink-source relationship may lead to less sucrose being synthesized in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves and fast-growing fruits belong to the “source” and “sink” organs in cucumber. Cucumber is a typical raffinose family oligosaccharide (RFO)-transporting plant, determining that the sink-source regulation of cucumber differs from sucrose-transporting model plants, such as Arabidopsis ( Arabidopsis thaliana ), rice ( Oryza sativa ) and tomato ( Solanum lycopersicum ) [ 14 , 15 , 16 , 17 ]. The proportion of RFO in cucumber leaf assimilates is up to 80%, which is unique to RFO-transporting plants [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the heavy carbohydrate accumulation of leaves can repress photosynthesis and regulate sugar distribution in plants (Goldschmidt and Huber 1992 ; Ainsworth and Bush 2011 ). Several studies have shown that sink strength plays a crucial role for controlling plants growth and the rate of photosynthetic activity in source leaves (Sonnewald and Fernie 2018 ; Xu et al 2021 ; Cabon et al 2022 ; Dai et al 2023 ). The activities associated with high sink growth need to consider not only the efficiency of photo-assimilate production and sucrose transport, but also the sink's capacity to utilize carbohydrates (Chen et al 2019 ; Jiang et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%